ANALISIS PENGARUH PENERIMAAN DAERAH, INVESTASI DAN TENAGA KERJA TERHADAP PDRB PROVINSI KALIMANTAN BARAT - B2051132001, NOVAN NUGRAHA PRATAMA (Jurnal Ekonomi Daerah (JEDA), 2016)
This research aimed to analyze the influence of local revenues, investment and labor to the Gross Regional Domestic Product (GRDP) of West Borneo Province during the period 2009-2013 research was motivated by the fact that the the Gross Regional Domestic Product (GRDP) of West Borneo Province is very volatile and the value is far behind compared to other provinces in the island of Borneo in the period of observation that this same. This research using panel data on a time series of 2009-2013 and using regression analysis